THE ROLE OF MICROFINANCE IN THE ECONOMIC PERFORMANCE OF PETTY TRADERS IN PENANG: THE CASE OF PROGRAMS TITIAN SAKSAMA RAKYAT BY PENANG DEVELOPMENT CORPORATION - Yusoff, Dalilah; Omar, Mohd Zaini; Hassan, Fatimah (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
This paper aims to examine the impact of the Program Titian Saksama Rakyat (PTSR) to the petty traders. PTSR is a microfinance program which focuses on the growth and the development of the micro entrepreneurs in Penang, Malaysia. It was initiated by the Penang Development Corporation (PDC) in co-operation with the Penang State Government in November 2008. Based on the sample of 150 petty traders involved in various business activities, the results showed that the amount of the loan received has a significant effect on their income. In addition, this study revealed that the amount of the loan received and the actual amount of the loan application (whether it is fully approved or not) were significantly affect the success of these traders. The results of the analysis also indicated that, the traders enjoyed significant benefits from the PTSR as this program was able to increase their income, expand their business, lift them out of poverty, improve their ability to increase the amount of deposits and their property, improve the quality of their health and improve their ability to own a house and land. Because of these benefits, these traders are interested and plan to apply for another loan from the PTSR program. This study, therefore, suggests that the PTSR program should be continued as it played significant roles in improving the socio-economic performance of the petty traders.